2020
DOI: 10.12659/msm.927654
|View full text |Cite
|
Sign up to set email alerts
|

A Chinese Retrospective Multicenter Study of First-Line Chemotherapy for Advanced Pancreatic Cancer

Abstract: Background Pancreatic cancer (PC) is a common digestive system tumor. For patients with advanced pancreatic cancer (APC), chemotherapy is still the predominant treatment. However, no large-scale clinical studies have been done of it as first-line therapy for APC. The goal of the present study was to assess real-world outcomes with chemotherapy in that setting. Material/Methods We retrospectively analyzed data from 322 patients with APC who were treated with chemotherapy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…At this stage, we can only speculate that this controversial result may relate with the inherent risk of confounding and selection bias. The efficacy of 21-day nab-P/Gem chemotherapy was consistent with published retrospective studies, 15 , 16 and the OS of this modified regimen seemed to be comparable with the OS of the traditional 28-day regimen reported by recent real-world studies listed in Table 3 . 17 , 18 …”
Section: Discussionsupporting
confidence: 88%
“…At this stage, we can only speculate that this controversial result may relate with the inherent risk of confounding and selection bias. The efficacy of 21-day nab-P/Gem chemotherapy was consistent with published retrospective studies, 15 , 16 and the OS of this modified regimen seemed to be comparable with the OS of the traditional 28-day regimen reported by recent real-world studies listed in Table 3 . 17 , 18 …”
Section: Discussionsupporting
confidence: 88%
“…The results showed that the median overall survival of gemcitabine-based combination chemotherapy and nab-paclitaxel plus S1 was better than gemcitabine monotherapy with statistic significant (TableS 5 and Fig 1S A-F Supplement). Our team retrospectively analyzed multicenter first-line chemotherapy regimens of advanced pancreatic cancer, the results showed that nab-paclitaxel plus S1 was not inferior to nab-paclitaxel plus gemcitabine or FOLFIRINOX (5-fluorouracil, leucovorin, irinotecan, and oxaliplatin) [ 28 ]. However, the final model did not incorporate chemotherapy regimens or laboratory markers levels at 6 weeks, unless these changes were shown statistically significant by multivariate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…In our center, we treated approximately seventy of our patients between 2015 and 2021 with rst-line Nab-Paclitaxel plus S-1, and only a very small proportion with FOLFIRINOX. The e cacy and safety of nab-paclitaxel plus S-1 as the rst-line treatment in patients with locally advanced and metastatic PDA have been demonstrated in previous study of our center and given these preclinical and preliminary clinical data, the combination of nabpaclitaxel and S-1 could theoretically be an option for pancreatic cancer [16,17].…”
Section: Discussionmentioning
confidence: 95%